Strategies affecting sustainable financial performance (A case study on southeast asian companies) - Ellice Josephine Ongkodjojo; Juniarti Juniarti (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to find out the effect of cost leadership and differentiation strategies on sustainable financial performance, including which strategy has a more dominant effect. Sustainable financial performance is financial performance that can be achieved and enjoyed into the future, not just for temporary in a certain period. The sample includes public companies in the Southeast Asia region consisting of 395 companies during the period 2107-2020, with a total 1,580 observations. This study uses Structural Equation Modeling to analyze the data. The test results show that the cost leadership strategy has no effect on sustainable financial performance. In contrast, the differentiation strategy has a positive and significant effect on sustainable financial performance. The role of innovation is very important in achieving sustainability. This study proves that innovation moderates the effect of the two strategies on sustainable financial performance. This study failed to prove which strategy has a more dominant effect due to the different results of the effect of the two strategies on sustainable financial performance.